The Influence of Bank Interest Rates on Home Sales Before and After The Covid-19 In Indonesia - Salim, Hockey; Alfarisi, Ade Salman; Sumawidjaya, Riyandi Nur; Sajekti, Tjipto; Luntungan, Irving Ignatius Paul; Merliana, Vina; Setiyani, Aris; Kusumawardani, Astrin (Dinasti International Journal of Education Management and Social Science, 2025)
This research explores how changes in bank interest rates affected home sales in Indonesia, both before and after the Covid-19 pandemic, placing importance on the connection between interest rate changes and the real estate market's behavior. A quantitative analysis of data regarding interest rates, volumes of home sales, and relevant economic indicators shows that notable interest rate decreases before the pandemic generally aligned with an increase in home sales, which reflects the usual housing market reaction to more accessible financing. Post-pandemic, the analysis indicates a more complex interaction. Even with sustained low-interest rates, home sales saw a substantial decrease, likely due to increased economic uncertainty and shifting consumer preferences, in most cases influenced by the pandemic. These observations emphasize the importance of grasping market sentiment and purchasing behaviors, suggesting that healthcare crises can significantly alter economic activities, like real estate. Furthermore, the implications extend beyond real estate, advising policymakers and financial institutions to develop interest rate strategies that consider the changing landscape of consumer behavior in health-related crises. The study ultimately provides important insights into the housing market's resilience during external shocks and the role of financial policies in supporting economic stability amidst public health emergencies, therefore guiding effective economic recovery efforts.